A study of congenital malformation in new born in Lagos, Nigeria - Lesi, Folorunso Ebun Akinboye (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 1969)
Summary: Some historical notes of the knowledge and beliefs regarding congenital malformations were reviewed. Based on a survey carried out at the Lagos Island Maternity Hospital, Nigeria, amongst 16,720 consecutive deliveries, an incidence of overall congenital malformation was discovered to be 14.8/1000 live and still births. This figure is similar to the incidence found by most workers in other parts of the world. The frequency of major defects was 6.8/1000. These figures reflect the congenital anomalies discernible at birth only. The increasing literature on the aetiology of congenital defects was reviewed. Although the author reviewed the increasing literature on the known aetiology of congenital defects, many of the factors considered by other workers could not be investigated in the present study. Non-specific environmental factors were therefore examined. Some of these are: Maternal Age -- Maternal Condition During Pregnancy -- Maternal Nutrition -- Birth Rank -- Social Class. These are discussed in general and also in relation to different anatomical systems. The perinatal outcome of the babies was studied. Clearly, bony defects were the most frequent congenital abnormality discernible at birth. The commonest of such was polydactyly and its incidence alone was found to be 8.7/1000 out of the total of 10.7/1000 of all skeletal defects. Of statistical significance in this study was the previous history of defects in the family of cases of congenital defects and also was anaemia in the group of mothers of cases. There was a predominance of hypoproteinaemia in the cases over the controls but a statistically significant result was not found in the total serum protein estimations. It was established that a precarious state of nutrition existed in the population studied as a whole. Because of the high frequency of polydactyly, the condition was specially studied. Fifty infants with extra digits born in the same hospital were analysed with regard to the anatomical distribution of the anomaly. Mother’s age, Birth Rank of the Children, Sex of the Cases and their Family History were investigated. It was discovered that ulnar polydactyly is the main digital anomaly found in Nigeria, and had a strong genetic background. 54% of the cases studied had bilateral ulnar supernumerary digits. When it occurred unilaterally, it affected only the left hand. The condition shows a higher frequency in babies born to mothers over the age of 30. There is a preponderance in favour of male (62%) There was no evidence that polydactyly is associated with major defects, it usually occurs as an isolated anomaly. Conclusions: -- i. As found in this Lagos survey, the over-all incidence of congenital malformation is similar to the frequencies found by most workers, -- ii. There are however racial differences in occurrence of individual defects: e.g. anencephaly and other C.N.S. defects have a high frequency amongst the Europeans; polydactyly amongst the Africans; and cleft lip and palate amongst the Chinese. – iii. The causes of the majority of congenital defects are not yet known. There is however, an increasing evidence that they are familial. In sporadic cases of multiple abnormality a genetic mutation is at fault. – iv. A further study of families of cases end a continued research into cytogenetics may reveal more facts concerning congenital abnormalities.
Keywords: Medicine, Ph.D.; Ph.D. Trinity College Dublin